Atomic resolution structure determination by the cryo‐EM method MicroED. (19th August 2016) - Liu, Shian; Hattne, Johan; Reyes, Francis E.; Sanchez‐Martinez, Silvia; Jason de la Cruz, M.; Shi, Dan; Gonen, Tamir
Abstract: The electron cryo‐microscopy (cryoEM) method MicroED has been rapidly developing. In this review we highlight some of the key steps in MicroED from crystal analysis to structure determination. We compare and contrast MicroED and the latest X‐ray based diffraction method the X‐ray free‐electron laser (XFEL). Strengths and shortcomings of both MicroED and XFEL are discussed. Finally, all current MicroED structures are tabulated with a view to the future.